4P Marketing Mix Strategy in Increasing Sales PT. Intan Pariwara Palopo - Guritno, Riko; Herlina Sakawati; Andi Muhammad Rivai; Yusi Irensi Seppa (Business Research and Administration Innovation, 2025)
4P Marketing Mix Strategy in Increasing Sales of PT Intan Pariwara Palopo. Thesis of the Faculty of Social Sciences and Law, Business Administration Study Program, Makassar State University. Supervised by Herlina Sakawati and Andi Muhammad Rivai. This study aims to identify and analyze the 4P marketing mix strategy in increasing PT Intan Pariwara Palopo's sales. To achieve this goal, this study used a qualitative approach, this study took 10 (ten) respondents, consisting of Branch Managers, Sales Representatives, postal sales, warehouses and consumers. Data collection procedures used were in-depth interviews and documentation. The interview technique was carried out in a structured manner using interview guidelines. The results of this study indicate that PT Intan Pariwara Palopo has implemented a good and effective marketing mix strategy in accordance with the theory of Kotler & Keller. In implementing the marketing mix, PT Intan Pariwara Palopo conducted product, price, place and promotion research to determine a marketing strategy.